Outcomes of patients with Cholesterol crystal embolism treated by peritoneal dialysis: retrospective study from the RDPLF registry. - Angelo Testa; Emmanuel Chamorey; Frederic Lavainne; Christian Verger (RDPLF, 2022)
Cholesterol crystal embolisms disease (CED) is a systemic disease characterized by tissue ischemia and microinflammation related to occlusion of arterioles by microemboli from ulcerated atheromatous plaques. The kidney is one of the most affected organs, often requiring dialysis. Our study examines the outcomes of a cohort of patients with CED treated with peritoneal dialysis (PD). As anticoagulants can favor emboli, peritoneal dialysis may theoretically have an advantage. From the database of the French Language Peritoneal Dialysis Registry (RDPLF), between January 1, 1995, and December 31, 2021, we selected patients treated with PD for >90 days and with an age >18 years. On the basis of the variables of patient autonomy, diabetes, BMI, modified Charlson index, age, sex, pre-PD treatment, causes of death, causes of transfer to hemodialysis, and peritonitis, three types of survival were estimated (patient, technical, and composite). After adjustment by propensity scores and taking into account competitive risks, 2 groups of patients were constituted on the basis of baseline nephropathy: emboli group vs. control group. Patient survival and strict technical survival are not associated with the type of nephropathy (CED versus others). Composite technical survival (uncensored for deaths and transfers to hemodialysis) was only associated with cholesterol emboli nephropathy in the multivariate analysis adjusted for diabetes, autonomy, and age of the patient at the start of the dialysis treatment (p=0.011; 95% CI [0.736 [0.581-0.931]]). Our study from the RDPLF database shows no difference in technical and patient survival in a cohort of patients with CED vs. a control group. It also confirms that PD may represent an adequate choice in this pathology.